Avaliação preliminar da contaminação por BTEX, em água subterrânea de poços tubulares, no município de Natal-RN - Lopes, Verushka Symonne de Medeiros (2011)
Among the different types of pollutants typically attributed to human activities, the petroleum products are one of the most important because of its toxic potential. This toxicity is attributed to the presence of substances such as benzene and its derivatives are very toxic to the central nervous system of man, with chronic toxicity, even in small concentrations. The area chosen for study was the city of Natal, capital of Rio Grande do Norte, where samples were collected in six different areas in the city, comprising 10 wells located in the urban area, being carried out in three distinct periods March/2009, December / June/2010 and 2009, and were evaluated for contamination by volatile hydrocarbons (BTEX - benzene, toluene, ethylbenzene and xylenes), so this work aimed to assess the quality of groundwater wells that supply funding for public supply and trade in the urban area of the city of Natal, in Rio Grande do Norte, contributing to the environmental assessment of the municipality. The analysis of BTEX in water was performed according to EPA Method 8021b. Was used the technique of headspace (TriPlus TP100) coupled to high resolution gas chromatography with selective photoionization detector (PID) and flame ionization (FID) - model Trace GC Ultra, Thermo Electron Corporation brand. The procedure adopted allowed the detection of concentrations of the order of μg.L-1. Data analysis with respect to BTEX in groundwater in the area monitored so far, shows that water quality is still preserved, because it exceeds the limits imposed by the potability Resolution CONAMA Nº. 396, April 2008